2008
DOI: 10.1126/science.1153629
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic CARD11 Mutations in Human Diffuse Large B Cell Lymphoma

Abstract: Diffuse large B cell lymphoma (DLBCL) is the most common form of non-Hodgkin's lymphoma. In the least curable (ABC) subtype of DLBCL, survival of the malignant cells is dependent on constitutive activation of the nuclear factor-kappaB (NF-kappaB) signaling pathway. In normal B cells, antigen receptor-induced NF-kappaB activation requires CARD11, a cytoplasmic scaffolding protein. To determine whether CARD11 contributes to tumorigenesis, we sequenced the CARD11 gene in human DLBCL tumors. We detected missense m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
796
2
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 779 publications
(844 citation statements)
references
References 25 publications
32
796
2
8
Order By: Relevance
“…31,32 This spontaneous complex formation was correlated previously with constitutive, receptorindependent, NF-kB activation. Here, we analyzed the subcellular distribution of DDK-CARD11 proteins by immunofluorescence after transfection into HEK 293 cells.…”
Section: Mutant Card11 Assembles In Cytoplasmic Aggregates Associatedsupporting
confidence: 65%
See 1 more Smart Citation
“…31,32 This spontaneous complex formation was correlated previously with constitutive, receptorindependent, NF-kB activation. Here, we analyzed the subcellular distribution of DDK-CARD11 proteins by immunofluorescence after transfection into HEK 293 cells.…”
Section: Mutant Card11 Assembles In Cytoplasmic Aggregates Associatedsupporting
confidence: 65%
“…The mechanism for NF-kB activation by CARD11 variants in the CARD and coiled-coil domain has been described. 29,31 For those cSCC variants within the C-terminal, membrane-associated GUK region that lead to enhanced NF-kB activity, a likely mechanism is a negative regulatory function in keeping with the importance of the SH3 and GUK domains for CARD11-mediated NF-kB signaling. 37 SH3 and GUK domains likely regulate activity by controlling subcellular localization and crucial proteineprotein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies showed that chromosomal rearrangements at the NFKB2 locus occur in a variety of human lymphomas (Rayet and Gelinas, 1999). Other changes to NF-kB family proteins in cancer tissues include the amplification and mutation of REL (c-Rel) in leukemia and lymphomas (Rayet and Gelinas, 1999;Starczynowski et al, 2007); mutations in the IKBA (IkBa) gene and hemizygous frameshift mutations in IKBE (IkBe) in Hodgkin's lymphoma (Cabannes et al, 1999;Scolnick and Halazonetis, 2000) (Emmerich et al, 2003); the amplification and overexpression of the IKBKE (IKKe) gene, a member of the IKK family, in breast cancer cell lines and patient-derived tumors (Boehm et al, 2007); and the mutation or amplification of TRAF2, TRAF3, CYLD, CIAP2, CD40, LTBR, TACI, NIK, CARD11 and other activators of the NF-kB signaling pathway in several cancer types (Campbell et al, 1998;Keats et al, 2007;Lenz et al, 2008). In our study, several NF-kB target genes (IL8, ZFP36, CXCL1 and IL12A) were downregulated in response to CHFR overexpression (Figure 1b).…”
Section: Discussionmentioning
confidence: 99%
“…NF-kappa B (NF-κB) or Rel proteins comprise a family of Protein Cell & tence of NF-κB in the nucleus, is shown in a wide variety of tumor types, such as lymphoma, liver cancer, lung cancer, breast cancer, etc (Mann et al, 2006;Qiao et al, 2006;Baby et al, 2007;Lenz et al, 2008). Besides, NF-κB is activated in response to tobacco, stress, dietary agents, obesity, alcohol, infectious agents, irradiation, and environmental stimuli that commonly contribute to carcinogenesis.…”
Section: Nf-κb Signaling Transduction Pathwaymentioning
confidence: 99%